Strategi Manajemen terhadap Produktivitas Tenaga Kerja pada Suatu Perusahaan Outsorsing - Denny Cahya Jaya Putra; Agung Dwi Nugroho (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
Labor productivity is a key aspect of the success of outsourcing companies. The purpose of this study is to analyze the management strategies used to improve labor productivity in outsourcing companies. The research method used is qualitative research by collecting data through observation and interviews. The results show that strategies such as training, motivation, verbal advocacy and effective communication can improve labor productivity. In short, implementing the right management strategies can improve employee efficiency and performance, and help them achieve their goals.